Patient selection for liver transplantation. (August 2013) - Carrion, Andres F; Aye, Lydia; Martin, Paul
Improved outcomes in liver transplant recipients reflect advances in surgical technique, post-operative care, immunosuppression as well as better selection of potential candidates. The pre-transplant evaluation is a multidisciplinary process intended to recognize and treat important comorbid conditions that may impair outcomes during the peri- and post-transplant periods. Important psychosocial issues should also be ascertained and tackled early during the pre-transplant evaluation with an overarching intention to improve the success of liver transplantation.